Scope of the narrative in the educational field from Time and Narrative by Paul Ricoeur - Ramírez Bonilla, Gerardo (Universidad Antonio Nariño, 2021)
The following article’s objective is to analyze the fourth chapter: World of the text toward the World of the reader from Volume III of Time and Narrative by Paul Ricoeur highlighting the use of narrative as a tool for communication between the reader and the author. Because of the length of the article, not all the concepts that Ricoeur used will be explained with extraordinary intensity. This article will however point out the most important information that focuses on reflexive hermeneutical approach that will contribute to the discussion about the narrative and how it can be based upon an essential element within the Educational field.